A Snapshot on Conversational Analysis - Muhamad Ahsanu (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
This article is exposed to scrutinize one of salient ideas in pragmatics. In this niche, we are centrally concerned with the organization of conversation. Key definitions will come up along the article, and the conversations analyzed here are borrowed from a readily available textbook of linguistics, in which two or more participants freely alternate in speaking, which generally happens outside specific institutional settings. This article tries to look into conversations, pragmatic phenomena. This also proposes a theo-retical phase for a conversational analysis and therefore helps students understand the procedures in analyzing co-present conversational participants. To a certain extent, presupposition may be seen in some basic ways organized around a conversational setting: the way in which information has to be presented if it is to be introduced to particular participants with specific share assumptions and knowl-edge about the world they are in. Key words: Pragmatics, Conversational Analysis, Language Usage.